Hubungan Paritas dan Menikah Usia Dini dengan Hasil Pemeriksaan Inspeksi Visual Asam Asetat (IVA) - Sri Sumarni; Laylatul Hasanah (Fakultas Ilmu Kesehatan, 2020)
Cervical cancer is a neoplasm or malignancy in the cervix. The problem of cervical cancer in Indonesia is very distinctive, namely that many and more than 70% of cases are found at an advanced stage when they come to the hospital. One of the screening tools for cervical cancer is the IVA method. A positive IVA test is thought to be a precancerous lesion. IVA stands for Acetic Acid Visual Inspection. This method of examination is done by smearing the cervix or cervix with acetic acid. According to a preliminary study at Puskesmas Rubaru Kab. Sumenep found that from the results of the IVA examination, there were 10 women who tested positive for the IVA test (12%). The aim of this study was to analyze multiple children and sexual relations at a young age with the results of the IVA test. This research method is analytic with cross sectional approach. The total population is 72 people, the sample of this study is based on a sample size formula of 60 people who meet the inclusion criteria. The results showed that most of the age at first marriage were WUS ≤ 16 years, as many as 36 WUS (60%), almost half of WUS had children> 1 x, namely 18 WUS (30%), and a small proportion of WUS got positive results during the examination IVA tests were 10 WUS (16.7%). Based on the statistical test of each variable, it shows p value <α, so that H1 is rejected, meaning that there is a relationship between parity and early marriage with the results of the IVA test at the Rubaru Community Health Center, Rubaru District, Sumenep Regency.